2019
DOI: 10.3389/fgene.2019.01041
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Response Can Be Predicted With Interpretable Multi-Variate Classifiers Exploiting DNA-Methylation and miRNA Data

Abstract: To address the problem of resistance to paclitaxel treatment, we have investigated to which extent is possible to predict Breast Cancer (BC) patient response to this drug. We carried out a large-scale tumor-based prediction analysis using data from the US National Cancer Institute’s Genomic Data Commons. These data sets comprise the responses of BC patients to paclitaxel along with six molecular profiles of their tumors. We assessed 10 Machine Learning (ML) algorithms on each of these profiles and evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 77 publications
1
34
0
Order By: Relevance
“…Given their suitability for high-throughput experiments [49], they are also the model for which most phenotypic and pharmacological information is publicly available. For many drugs, only much smaller amounts of pharmacogenomics datasets, if any, has been released using more patient-relevant in vivo models [59][60][61][62]. Consequently, often the only data that can be used to predict drug sensitivity comes from cell lines, thus having their niche in guiding precision oncology efforts [55].…”
Section: Discussionmentioning
confidence: 99%
“…Given their suitability for high-throughput experiments [49], they are also the model for which most phenotypic and pharmacological information is publicly available. For many drugs, only much smaller amounts of pharmacogenomics datasets, if any, has been released using more patient-relevant in vivo models [59][60][61][62]. Consequently, often the only data that can be used to predict drug sensitivity comes from cell lines, thus having their niche in guiding precision oncology efforts [55].…”
Section: Discussionmentioning
confidence: 99%
“…11,18 Third, the first prospective results of a CNN-based SF are not better in any way to those using more established ML algorithms (Table 4). Last, as any other ML algorithm, DL algorithms are not optimal for many supervised learning problems 17,[19][20][21][22] and SBVS could easily be another one of them.…”
Section: What Are the Limitations Of Commonly Used Retrospective Bencmentioning
confidence: 99%
“…17 We will not use the term AI in this review because it conveys the notion that a categorical change has occurred with respect to ML, which is not the case in the research area of SF development, 11,18 as well as in many others. 17,[19][20][21][22] The term AI is, however, appropriate as a reminder of aspirations and achievements. ML-based SFs reached long time ago the level where it is able to identify new potent actives better than a human expert would do using the same training data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent study discussing their role in cell resistance to taxanes was performed by Chen et al [ 113 ], who identified two miRNAs, miR-335-5p and hsa-let-7c-5p, and their gene targets, chemokine (C-X-C motif) ligand 9, C-C chemokine receptor type 7, and suppressor of cytokine signaling 1, which are all linked to cell resistance to taxanes. Certain miRNA profiles are typical for paclitaxel-sensitive or chemoresistant tumors; these molecules could be used in the initial screening preceding the personalized treatment of cancer patients [ 114 ].…”
Section: Introductionmentioning
confidence: 99%